Juridical Analysis of The Regulation of NIK as NPWP in The Taxation System in Indonesia - Esfandiari, Fitria; Tongat, Tongat; Retno Meilani (Audito Comparative Law Journal (ACLJ), 2024)
Entering the era of modernization, the government has introduced regulations regarding the use of the Population Identification Number (NIK) as the Taxpayer Identification Number (NPWP). The purpose of this research is to determine the juridical analysis of the regulation of NIK as NPWP in the Indonesian tax system and to establish the ideal concept of integrating NIK as NPWP in the Indonesian tax system. The research method employed is a juridical-normative approach with a legislative perspective, conceptual approach, and literature study. The results of this research indicate that the regulation of NIK as NPWP will serve as a foundation for the profile of Individual Taxpayers (WP OP). The concept of integration will be carried out by the Minister of Home Affairs, who will provide population data and feedback data from users to the Minister of Finance, which will then be integrated into the tax database. As a result, cooperation will be established in the data management process to align and synchronize NIK with NPWP. This aligns with the concept of Collaborative Governance in achieving One Data Indonesia through the Harmonization of Tax Regulations Act (UU HPP).